2019
DOI: 10.1177/1362168819890825
|View full text |Cite
|
Sign up to set email alerts
|

Understanding willingness to communicate in L2 between Korean and Taiwanese students

Abstract: This study examined Korean ( n = 143) and Taiwanese ( n = 261) EFL students’ willingness to communicate in a second language (L2 WTC) in in-class, out-of-class, and digital settings. Follow-up interviews ( n = 20) were also conducted to identify factors that might have influenced their L2 WTC. Results showed that Korean and Taiwanese participants scored lowest on L2 WTC inside the classroom. The qualitative data suggest that L2 speaking anxiety might have equally influenced both groups’ L2 WTC. Additionally, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 59 publications
(128 reference statements)
0
16
0
Order By: Relevance
“…The questionnaire used in the study consisted of three parts—(1) L2 WTC, (2) IDLE and (3) demographic data. The L2 WTC Scale, which had been employed in a comparative study of L2 WTC (Lee et al, 2019), is a five‐item questionnaire that was used to measure L2 WTC in the classroom (‘When you are given a chance to talk freely in an English class’; five items). All items were marked on 5‐point Likert scale (1 = definitely not willing; 5 = definitely willing).…”
Section: Methods and Data Sourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…The questionnaire used in the study consisted of three parts—(1) L2 WTC, (2) IDLE and (3) demographic data. The L2 WTC Scale, which had been employed in a comparative study of L2 WTC (Lee et al, 2019), is a five‐item questionnaire that was used to measure L2 WTC in the classroom (‘When you are given a chance to talk freely in an English class’; five items). All items were marked on 5‐point Likert scale (1 = definitely not willing; 5 = definitely willing).…”
Section: Methods and Data Sourcesmentioning
confidence: 99%
“…Lee et al (2020) extended Lee et al’s (2019) comparative study by investigating L2 WTC between Korean and Swedish secondary school students (both groups aged 16–19 years). The researchers indicated that different educational (eg, test‐oriented vs. communicative‐oriented pedagogy), socio‐linguistic (eg, monolingual vs. multilingual residents) and socio‐cultural environments (eg, a homogeneous vs. an ethnically diverse society) might have uniquely influenced the Korean and Swedish cohorts’ level of L2 motivation and attitudes towards English accents, which, subsequently, might have led to different levels of L2 WTC in the classroom.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies investigated the relationship among teacher immediacy, teacher–student rapport, and learners’ motivation, learners’ engagement, satisfaction, and their learning outcomes ( Hsu, 2010 ). In recent years, some studies have focused on recognizing the teacher–student relationship as a contextual topic ( Lee et al, 2019 ). Burke-Smalley (2018) argued that culture and context might impact teacher immediacy and teacher–student rapport and their willingness to communicate in EFL contexts.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Psychological or moral actions include tasks, such as motivating, persuading, rewarding, punishing, and planning. In addition to logical and psychological actions, teachers also refer to ethical teaching actions in which the teachers demonstrate characteristics, such as honesty, courage, tolerance ( Pishghadam et al, 2021b ), compassion, respect, and fairness ( Lee et al, 2019 ). Communication with teachers and the quality of their acceptance improve students’ motivation in academic activities ( Fallah, 2014 ), and their emotional and social performance ( Henry and Thorsen, 2018 ).…”
Section: Introductionmentioning
confidence: 99%